(3JdGbi GdCQH aj eQGbi GdCOH (B((3OjhGf TYQ (B)s - (3YHO GdQMef GdUaJj GdTQbGhj,J (B1264 (3g` s
(3ChdgG (B:s
(3CeG HYO (B: (3aEf UOQ GdOhdI GdYKeGfjI CMeO GafOi dMXfi HYjf GdaQGSI hGdSeGMI , hZdb bGajJi ai cYH GdaUGMI hCeQfi Cf CVef gPG GdeLehY eG SfM HNGWQi hChOY UOQg CSQGQ VeGFQi s
(3BNQgG (B:s
(3aEf QShd Gddg (B((3SdjeGf(B) (3NGWH fedI , hEf Edg GdYQT ChMi Edi GdfMd , hEf JaVdJe HJHdjZ GdSdGe def jdhP Hce ce Ydi QHce s
(3CfTCg HCeQ ef UOQ GdOhdI GdYKeGfjIQJHI Ydi MQha GdgLGAs
(3hGfXQ GdLRA GdChd HQbe (B147 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B309 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B142s
Keywords: (3GdCOHs